The Strength-Endurance Continuum revisited: a critical commentary of the recommendation of different loading ranges for different muscular adaptations - Fisher, J. P.; Steele, J.; Androulakis-Korakakis, P.; Smith, D.; Gentil, P.; Giessing, J. (Journal of Trainology, 2020)
The accepted wisdom within resistance training is that differing loads and corresponding repetition maximum (RM) ranges are optimal for inducing specific adaptations. For example, prominent organizations and their respective publications have typically prescribed heavy loads for maximal strength increases (>85% 1RM/<6RM), more moderate loads for hypertrophy (67-85% 1RM/6-12RM) and lighter loadsfor local muscular endurance (LME; <67% 1RM/>12RM). Since we believe these recommendations originate from a misunderstanding and misinterpretation of DeLorme`s strength-endurance continuum, the aim of this narrative review is to discuss the preponderance of research surrounding training load and strength and LME adaptations. Design & Methods:Narrative Review Results:The current body of literature fails to support recommendations for the use of specific loads for specific strength, hypertrophy or LME adaptations. Furthermore, that the strength-endurance continuum originally presented by DeLorme was never intended to compare the use of heavier-and lighter-load resistance training, but rather to consider the adaptations to strength training and aerobically based endurance exercise. Finally, a this adaptation. Conclusions: The body of research supports that absolute LME appears to adapt as a result of maximal strength increases. However,relative LME shows minimal response to strength training with either heavier-or lighter-loads. We present the limitations of the current body of research and promote specifically detailed recent research as well as the importance of generality of strength and LME in both sporting and real-world settings